3(4x-1.3)=5x-3.9

Simple and best practice solution for 3(4x-1.3)=5x-3.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-1.3)=5x-3.9 equation:


Simplifying
3(4x + -1.3) = 5x + -3.9

Reorder the terms:
3(-1.3 + 4x) = 5x + -3.9
(-1.3 * 3 + 4x * 3) = 5x + -3.9
(-3.9 + 12x) = 5x + -3.9

Reorder the terms:
-3.9 + 12x = -3.9 + 5x

Add '3.9' to each side of the equation.
-3.9 + 3.9 + 12x = -3.9 + 3.9 + 5x

Combine like terms: -3.9 + 3.9 = 0.0
0.0 + 12x = -3.9 + 3.9 + 5x
12x = -3.9 + 3.9 + 5x

Combine like terms: -3.9 + 3.9 = 0.0
12x = 0.0 + 5x
12x = 5x

Solving
12x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
12x + -5x = 5x + -5x

Combine like terms: 12x + -5x = 7x
7x = 5x + -5x

Combine like terms: 5x + -5x = 0
7x = 0

Divide each side by '7'.
x = 0

Simplifying
x = 0

See similar equations:

| 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 | | 3.1x-37=2.1x+8 | | Y=-2+3(4) | | 1.8x+1-2.8x=4 | | Y=-2+3(3) | | (((2y^0)*(2xy^0))/(-xy^4))^-4 | | -3(3s-6)-18=-3(7s+3)-5 | | Y=-2+3(2) |

Equations solver categories